IMPLEMENTATION OF DESIGN THINKING TECHNOLOGY IN THE TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS - Tiahur, Vasyl (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article presents the results of a theoretical analysis of the need to prioritize the development of technological education as an important factor in creating a new quality education system. The purpose of the study is to theoretically justify the need to prioritize the implementation of technological education in general educational institutions at the current stage of educational progress. An analysis of the concept of "technological education", methods and forms of its implementation in general educational institutions, "scientific and technical progress", "technological crisis" was carried out. It was established that the technological leap is increasingly affecting various types of spiritual production. Global trends in the development of economies and production, which meet the needs of humanity, require more and more professions related to technology and high-tech production and related to natural sciences. All this requires a wider and updated implementation of technological education in the educational process of general educational institutions. Results were obtained using the method of theoretical analysis and study of information sources and statistical data. The results. It was revealed that a crisis is brewing in Ukraine in providing technological industries with specialists in engineering and labor specialties. Proposals were made for the popularization of technologies in school, the introduction of their elements into the study of school subjects, increasing their perspective, significance and prestige in society. It was concluded that this issue requires new scientific research, the development of thorough scientific and methodological support for its use in education, and especially in ensuring orientation for the training of schoolchildren as future specialists in technological, labor, and engineering specialties. It is necessary to determine the priority directions of technology development, modern trends in education and directing schoolchildren to acquire technological and engineering specialties, both at the level of vocational and technical education and at the level of higher education. Orientation to technological professions should take into account universal human values and psychological needs of a person